A New Method for the Order Reduction of Multivariable Systems Using Bilinear Transformation and Time Moments Matching Technique - G.V.K.R. Sastry, Dr.; G. Surya Kalyan, Dr.; Tejeswara Rao, K. (International Journal of Engineering and Technology, 2018)
This paper proposes a new order reduction procedure for high order continuous-time MIMO systems.Â The denominator of the low order model is obtained using a Bilinear transformation whereas the Moment matching method is used to obtain the numerator. The reduced order system obtained by this method gives better approximation than some of existing methods.Â Â